Environmental DNA enables detection of terrestrial mammals from forest pond water. (11th June 2017) - Ushio, Masayuki; Fukuda, Hisato; Inoue, Toshiki; Makoto, Kobayashi; Kishida, Osamu; Sato, Keiichi; Murata, Koichi; Nikaido, Masato; Sado, Tetsuya; Sato, Yukuto; Takeshita, Masamichi; Iwasaki, Wataru; et al.
Abstract: Terrestrial animals must have frequent contact with water to survive, implying that environmental DNA (eDNA) originating from those animals should be detectable from places containing water in terrestrial ecosystems. Aiming to detect the presence of terrestrial mammals using forest water samples, we applied a set of universal PCR primers (MiMammal, a modified version of fish universal primers) for metabarcoding mammalian eDNA. The versatility of MiMammal primers was tested in silico and by amplifying DNAs extracted from tissues. The results suggested that MiMammal primers are capable of amplifying and distinguishing a diverse group of mammalian species. In addition, analyses of water samples from zoo cages of mammals with known species composition suggested that MiMammal primers could successfully detect mammalian species from water samples in the field. Then, we performed an experiment to detect mammals from natural ecosystems by collecting five 500‐ml water samples from ponds in two cool‐temperate forests in Hokkaido, northern Japan. MiMammal amplicon libraries were constructed using eDNA extracted from water samples, and sequences generated by Illumina MiSeq were subjected to data processing and taxonomic assignment. We thereby detected multiple species of mammals common to the sampling areas, including deer ( Cervus nippon ), mouse ( Mus musculus ), vole ( Myodes rufocanus ), raccoon ( Procyon lotor ), rat ( Rattus norvegicus ) and shrew ( Sorex unguiculatus ). Many previous applications of the eDNA metabarcoding approach have been limited to aquatic/semiaquatic systems, but the results presented here show that the approach is also promising even for forest mammal biodiversity surveys.